Solvent- and catalyst-free regioselective hydrophosphanation of alkenes - Alonso, Francisco (2012)
The hydrophosphanation of alkenes, an atom-economy process typically promoted by radicals or metal species, has been shown to take place in the absence of a catalyst, under solvent-free conditions and in a regioselective manner.